Simulasi Proses Distribusi dalam Peningkatan Kecepatan Pengiriman Dengan Pendekatan Business Process Improvement (BPI) - Vinda Ilman Nafiah; Putri Amelia (KOLONI, 2026)
This study aims to analyze and improve the product distribution process at PT. Mulia Jaya, which experiences delivery delays. The research employed a descriptive qualitative approach using the Business Process Improvement (BPI) method supported by Business Process Model and Notation (BPMN) modeling and simulation using Arena software. Data were collected through interviews, observations, and documentation to identify value-added and non-value-added activities. The results indicate that delays are caused by high waiting times and bottlenecks in the product preparation and loading processes. Simulation results in the existing condition show that the average total distribution process time is 5.45 hours. Scenario 1 was conducted by adding a server to the loading process, reducing the process time to 5.07 hours or by 6.97%. Meanwhile, Scenario 2 involved adding transportation resources, resulting in an average process time of 5.25 hours or a reduction of 3.58%. Based on the simulation results, Scenario 1 is considered the most optimal improvement alternative because it provides the greatest reduction in process time and improves distribution efficiency.